Comparison of diagnostic validity between mitotic activity index and Ki-67 expression as predictor for breast cancer in distant metastasis - Ginting, Andreasta; Setiawan, I. Gede Budhi; Sudarsa, I. Wayan; Widiana, I. Gede Raka (International Journal of Research in Medical Sciences, 2019)
Background: One particular cause of death from breast cancer is distant metastasis. In this study, we calculate and compare diagnostic value of Mitotic Activity Index (MAI) and Ki-67 expression in predicting distant metastasis. Methods: Study was conducted in Sanglah Hospital from January 2017 to February 2019. All histopathology results from open biopsy are examined, thus MAI and Ki-67 values were obtained. We divided this into 2 groups: MAI high (≥20/HPF), low (<20/HPF) and Ki-67 high (≥20%) and low (<20%). We compared with distant metastasis event as gold standard, obtained from radiology examination. We count all diagnostic characteristics (sensitivity, specificity, positive and negative predictive value, accuracy, and likelihood ratio). We compared these diagnostic validities from data area under curve (AUC) with p value <0.005 considered to be statistically significant. Results: A total of 173 breast cancer patients were participated in this study, 92 of them had distant metastasis (53.2%) and 81 patients didn’t have any distant metastasis (46.8%). MAI had relative high specificity (82.7%) and Ki-67 had fair sensitivity values (69.6%). There are 0.08 point AUC differences between these two variables. With p value higher than 0.05 (0.06), it can be summarized that these two variables are not different significantly and statistically. Conclusions: There is not any statistically significant difference between these two markers in predicting distant metastasis in breast cancer. We hope other researcher interest into exploring more about these markers and their function.